Peran Komunikasi Hindu Terhadap Perilaku Pemuda Yang Ajeg Bali di Tengah Pusaran Globalisasi - Bagus Ade Tegar Prabawa; Ni Komang Sutriyanti (Jayapangus Press, 2020)
In the era of globalization the development of science and technology is developing very rapidly. With the development of science and technology many foreign cultures / foreign cultures have entered Bali. Bali is one of the provinces in Indonesia which is known as the island of a thousand temples, so that a lot of Balinese culture is starting to fade. Youth plays a very important role in the success of a nation. Ajeg bali is an identity politics or movement to maintain Balinese ethnic identity that aims to restore Balinese society in the context of the experience of the teachings of Hinduism and Balinese culture (re-Balinization and re-Hinduisasi). Ajeg Bali is closely related to the implementation of the Tri Hita Karana concept in social life. Where the implementation of the steady Balinese concept is expected to create harmony in Bali and preservation of traditions and culture in Bali. Youth in Bali do not consider Ajeg Bali to be a stagnant concept but rather a conscious and sustainable modernization. In practice, Balinese youth are able to defend their identity and culture from the new values ​​and culture that globalization promotes. Cultural hegemony, has become quite painful for the people of Bali. Until then redefining the role of all elements of Balinese society, especially young people, trying to restore the meaning of Balinese culture and traditions in the daily breath of its people. Efforts to preserve the tradition above the Ajeg Bali movement lead to an increase in the strength of young Balinese so as not to fall into the conquest of global cultural hegemony. Bali's steady design even though it had to pass the commodification of the practical political interests of the authorities, but in its course this design was identified as a cultural movement.